Genetic diversity, transmission dynamics and drug resistance of Mycobacterium tuberculosis in Angola - Perdigão, João (2017)
The authors wish to thank the laboratory, clinical, and nursing staff of HDP, whose high quality of service and cooperation have made this study possible. Financial support was provided by the Fundacao para a Ciencia e a Tecnologia (FCT) Portugal [PTDC/SAU-EPI/122400/2010], part of the EDCTP2 program supported by the European Union. JP was supported by a post doc fellowship from project [PTDC/SAU-EPI/122400/2010] and by fellowship [SFRH/BPD/95406/2013] from FCT. JP is thankful to the European Society of Clinical Microbiology and Infectious Diseases for a Research Grant, and would like to acknowledge the Study Group for Mycobacterial Infections. DM was supported by FCT fellowship [SFRH/BPD/100688/2014] and DM, IC MV are thankful to [GHTM UID/Multi/04413/20139] from FCT. CS was supported by FCT [SFRH/BD/73579/2010].